2011
DOI: 10.1590/s0100-29452011000500073
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de fruto da aceroleira cv. Olivier em dois estádios de maturação

Abstract: RESUMO -A acerola é um fruto de grande potencial econômico e nutricional devido ao seu alto teor de vitamina C, destacando-se como alimento funcional. É comercializada principalmente na forma de polpa congelada e fruto in natura. O objetivo deste estudo foi avaliar a qualidade dos frutos da aceroleira cv. Olivier em dois estádios de maturação. Para tanto, foram colhidas amostras de frutos em um pomar comercial no município de Junqueirópolis-SP. Foram realizadas a determinação da cor externa dos frutos e anális… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 4 publications
4
20
0
2
Order By: Relevance
“…Sagar et al (2014) found lower values than the current study, 89.1% of antioxidant activity in fruits of mature acerola (red colour) produced in India. Similar to current work Adriano et al (2011) reported levels of 810.2 ± 53.3 mg of ascorbic acid 100 g -1 of pulp in Olivier ripe fruit. Higher levels, 3,629.6 mg of ascorbic acid 100 g -1 of pulp were found by Figueiredo Neto et al (2014), in mature fruits of Okinawa.…”
Section: Resultssupporting
confidence: 91%
“…Sagar et al (2014) found lower values than the current study, 89.1% of antioxidant activity in fruits of mature acerola (red colour) produced in India. Similar to current work Adriano et al (2011) reported levels of 810.2 ± 53.3 mg of ascorbic acid 100 g -1 of pulp in Olivier ripe fruit. Higher levels, 3,629.6 mg of ascorbic acid 100 g -1 of pulp were found by Figueiredo Neto et al (2014), in mature fruits of Okinawa.…”
Section: Resultssupporting
confidence: 91%
“…West Indian cherry (Malpighia emarginata) fruits are known for their pleasant taste, high contents of vitamin C, vitamin A, B-complex vitamins, iron, calcium (SÁ et al, 2017), anthocyanins and carotenoids, compounds which have beneficial effects on human health for their known antioxidant action (MACIEL et al, 2010). The crop is adapted to the most diverse climates and can be found in several regions of the planet, but its commercial cultivation is concentrated in tropical and subtropical regions (ADRIANO et al, 2011), such as those found in the Brazilian territory.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the Northeast is the main producing region, with 64% of the cultivated area in the country, corresponding to a mean yield of 15,360 kg ha -1 year -1 (ADRIANO et al, 2011;ESASHIKA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%